1995
DOI: 10.1172/jci117712
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide mediates cytotoxicity and basic fibroblast growth factor release in cultured vascular smooth muscle cells. A possible mechanism of neovascularization in atherosclerotic plaques.

Abstract: To define the pathophysiological role of nitric oxide (NO) released from vascular smooth muscle cells (VSMC), we examined whether NO released from VSMC induces cytotoxicity in VSMC themselves and adjacent endothelial cells (EC) using a coculture system. Prolonged incubation with interleukin-1 (IL-1) induced large amounts of NO release and cytotoxicity in VSMC. NG-Monomethyl-L-arginine, an inhibitor of NO synthesis, inhibited both NO release and cytotoxicity induced by IL-1. In contrast, DNA synthesis in cocult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
2
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 50 publications
0
57
2
2
Order By: Relevance
“…toxicity directly, NO may facilitate release of basic fibroblast growth factor from VSMC which, in turn, stimulates endothelial cell growth (39). Our data demonstrate a profound limitation of neointimal proliferation after a single, local administration of a durable, potent S-nitrosothiol.…”
Section: Discussionmentioning
confidence: 62%
“…toxicity directly, NO may facilitate release of basic fibroblast growth factor from VSMC which, in turn, stimulates endothelial cell growth (39). Our data demonstrate a profound limitation of neointimal proliferation after a single, local administration of a durable, potent S-nitrosothiol.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, Jamieson and co-authors have demonstrated a correlation between apo(a) deposition within endothelial cells of vasa vasorum and the stage of atherosclerotic plaque in human cerebral vessels (37), suggesting a specific link between apo(a) receptor and the pathogenesis of atherosclerosis. Increased angiogenic factor expression in the adventitia has been demonstrated by several investigators (4,24,26,(38)(39)(40). In addition, certain angiogenic factors are also vascular smooth muscle cell and endothelial mitogens (17, 39,41,42).…”
Section: Discussionmentioning
confidence: 94%
“…Others have suggested that FGF-2, which lacks a signal peptide for secretion, may be released in response to cell injury (45). Both oxidized LDL and lysoPC are known to injure cells, and vitamin E has been shown to inhibit the injury induced by oxidized LDL (9) and lysoPC.…”
Section: Resultsmentioning
confidence: 99%
“…FGF-2 lacks a signal peptide required for the cellular release of other secretory proteins (50). Results from a number of studies have suggested that cell injury can release FGF-2 (51), including a report that cell damage is required for FGF-2 secretion in cultured smooth muscle cells (45). However, it was reported that FGF-2 can be released from SMC without discernible injury by 25-hydroxycholesterol (52).…”
Section: Discussionmentioning
confidence: 99%